Creativity and Psychosis: An Analytical Psychology Approach. (2nd January 2022) - Howe, Andrew
ABSTRACT: Treatment of schizophrenia and other psychotic illnesses primarily uses antipsychotic medication. Compared to other common mental health conditions, the opportunities for psychotherapy in psychosis are limited. Jung and the post-Jungians considered that psychotherapy of psychosis is possible, supported by using creative arts and other individualized treatments. Moreover, they felt there was a tremendous creative potential within the symptoms of psychosis that could help patients develop and learn about themselves. This paper discusses the creative potential within psychosis and how it might be treated by reviewing Jungian literature and considering contemporary evidence for an analytical psychology understanding.